1985
DOI: 10.1161/01.hyp.7.3_pt_2.i101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypertension on migration and proliferation of smooth muscle in culture.

Abstract: SUMMARY Migratory and proliferative characteristics of explanted rat aortic smooth muscle cells were studied in response to hypertension induced by 4 weeks of deoxycorticosterone-salt administration. Under low serum conditions (0.1% fetal bovine serum), over 80% of aortic medial explants from hypertensive rats yielded smooth muscle cell colonies after 8 days of culture while fewer than 10% of the control explants were positive. Time lapse video analysis of subsequent growth in the presence of 10% serum reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
34
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 9 publications
3
34
0
Order By: Relevance
“…32 Platelet adherence to the intima is not typically present and neither is endothelial cell loss. We have observed increased motility of SMCs out of aortic explants obtained from hypertensive animals 38 and increased growth potential of such cells. 38 - 39 If similar changes also occur in vivo, then hypertension might stimulate medial SMCs to migrate into the intima where they could proliferate and contribute to the development of intimal thickening.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…32 Platelet adherence to the intima is not typically present and neither is endothelial cell loss. We have observed increased motility of SMCs out of aortic explants obtained from hypertensive animals 38 and increased growth potential of such cells. 38 - 39 If similar changes also occur in vivo, then hypertension might stimulate medial SMCs to migrate into the intima where they could proliferate and contribute to the development of intimal thickening.…”
mentioning
confidence: 72%
“…We have observed increased motility of SMCs out of aortic explants obtained from hypertensive animals 38 and increased growth potential of such cells. 38 - 39 If similar changes also occur in vivo, then hypertension might stimulate medial SMCs to migrate into the intima where they could proliferate and contribute to the development of intimal thickening. Many of the intimal changes caused by hypertension are broadly similar to those observed with aging or hypercholesterolemia.…”
mentioning
confidence: 72%
“…The K., however, was similar to that of cells from the WKY rat. There is abundant evidence for accelerated growth in culture of VSMC from the SHR (9,35,36), and several studies have shown participation of the Na+/H' antiporter in the initiation of cell growth (3,4,37). It is conceivable that increased growth rate in SHR cells may require recruitment of a greater number of antiporters in the plasma membrane or enhancement oftheir activity.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported for deoxycorticosterone acetate salt-induced hypertension, in which environmental conditions rather than genetics lead to an increase in smooth muscle cell proliferative potential. 37 This difference in the physiological activity of smooth muscle cells in primary and secondary hypertension could explain the greater intimal proliferation in SHRs.…”
mentioning
confidence: 99%